Trends in Estimation of Post-Mortem Interval Using Instrumental Analysis (Journal of Forensic Medicine & Toxicology, 2025)
The importance of estimating time since death has been acknowledged for centuries. One of the key elements in crime investigation lies in the reckoning of post-mortem interval(PMI). It’s evident why an accurate post-mortem interval estimation is needed in all criminal cases. There is ample literature regarding the techniques for estimating postmortem interval, but these techniques must be as precise, reliable, and scientific as possible. Conventional methods for determining PMI are fixed on physical, metabolic, autolysis, histochemistry, and physicochemical processes. These parameters are employed in the initial period of postmortem, and over time its reliability decreases. Recent research attempts the improvement of post-mortem interval estimation by more predictable and quantifiable parameters. This study presents the current headway in estimating time since death. Chemical changes in biological samples, Spectroscopical analysis for detection of biochemical changes, thanatomicrobiome analysis, predictable protein degradation process in human muscles, and dating of skeletal remains -improved the postmortem interval estimates. Further research is needed in these many parameters, the field still has a long way to go in terms of finding the exclusive formula for accurate post mortem interval estimation. This is a review that emphasizes several recent methods for precisely estimating post mortem intervals by instrumental analysis.
Keywords: Medico-Legal Examination; Post-Mortem Interval; Autolysis; Thanatomicrobiome; Spectroscopy.